Utilization of Artificial Intelligence-Based Learning Videos: Enhancing Learning Interest in Early Childhood Moral Education - Fatmawati, Nilal Muna; Raharjo (Program Studi Pendidikan Islam Anak Usia Dini, Fakultas Ilmu Tarbiyah dan Keguruan, UIN Sunan Kalijaga, Yogyakarta, 2024)
A common challenge in early childhood moral education is the low level of engagement and interest when using traditional storytelling methods. This study examines the implementation and utilization of artificial intelligence (AI)–based learning videos to enhance early childhood moral education at RA Hj. Sri Musiyarti, Semarang, Indonesia. With a qualitative case study approach, the research involved 20 children aged 4 to 5 years, with data collected through observations, semi-structured interviews with teachers, and documentation. The study focuses on the impact of AI-based videos on children's interest in moral learning, a shift from traditional storytelling methods to video-based learning. Findings reveal that AI-based learning videos significantly increase children's interest and engagement, promoting active participation in the classroom. The videos facilitated cognitive development and emotional engagement, making moral learning more enjoyable and effective. The reliability and validity of the findings were ensured through methodological triangulation and peer debriefing. The study concludes that AI-based learning videos are a powerful tool in fostering intellectual and emotional growth in early childhood, supporting innovative and exciting teaching approaches in moral education. The results suggest that AI technologies can enhance early childhood education, with future research needed to expand the scope of AI in education and to explore strategies for teacher training to ensure the effective implementation of AI technologies.